2015
DOI: 10.3109/21691401.2015.1041639
|View full text |Cite
|
Sign up to set email alerts
|

Clinical test to detect mecA and antibiotic resistance in Staphylococcus aureus, based on novel biotechnological methods

Abstract: The results of our study showed that 47% of S. aureus isolates were MRSA. Overall, in this research study, resistance to all test antimicrobial agents in MRSA isolates were higher than that of MSSA isolates. Our results also revealed that 85% of mecA-positive isolates and 15% of mecA-negative isolates were resistant to methicillin; while 96% of mecA-negative isolates were sensitive to methicillin. Meanwhile 4% of mecA-positive isolates were also sensitive to methicillin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…Studies have demonstrated that S. aureus usually forms biofilms in chronic wounds, thereby causing drug-resistance (52). Similar to findings by Shittu et al (53) and Shah et al (54), no strains of S. aureus, including those in the MRSA group, showed resistance to vancomycin in our study. However, high levels of resistance to tetracycline (79.2%), quinupristin/dalfotristin (70%), gentamicin (54.2%), and erythromycin (50.0%) were found in Enterococcus spp.…”
Section: Discussionsupporting
confidence: 90%
“…Studies have demonstrated that S. aureus usually forms biofilms in chronic wounds, thereby causing drug-resistance (52). Similar to findings by Shittu et al (53) and Shah et al (54), no strains of S. aureus, including those in the MRSA group, showed resistance to vancomycin in our study. However, high levels of resistance to tetracycline (79.2%), quinupristin/dalfotristin (70%), gentamicin (54.2%), and erythromycin (50.0%) were found in Enterococcus spp.…”
Section: Discussionsupporting
confidence: 90%